2018
DOI: 10.3390/su10051524
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Productivity Gains of Digital and Green Servitization: Implications from the Automotive Industry

Abstract: Abstract:The growing industrial concern about sustainability challenges has driven vehicle and auto parts manufacturers to adopt service capabilities as a way to maintain competitiveness in compliance with environmental regulations. As a result, automakers have progressively integrated digital and green service initiatives to support operations and address environmental issues effectively. The present study examined the effect of digital and green servitization on the firm's productivity. To test their effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 85 publications
(181 reference statements)
3
77
0
Order By: Relevance
“…More concretely, Figure 2 summarizes the various relationships that can be observed between PSI and performance. Exhibit (2a) shows a positive and linear relationship between these variables (Belvedere et al, 2013: Bustinza et al, 2015Crozet and Millet, 2017;Opazo et al, 2018;Szász et al, 2017), which points to an equally proportionate effect of service sales on performance, regardless the business' current service sales. One way of relaxing this assumption is to test for the presence of decreasing returns to PSI.…”
Section: Linear and Nonlinear Relationships Between Psi And Performancementioning
confidence: 99%
See 1 more Smart Citation
“…More concretely, Figure 2 summarizes the various relationships that can be observed between PSI and performance. Exhibit (2a) shows a positive and linear relationship between these variables (Belvedere et al, 2013: Bustinza et al, 2015Crozet and Millet, 2017;Opazo et al, 2018;Szász et al, 2017), which points to an equally proportionate effect of service sales on performance, regardless the business' current service sales. One way of relaxing this assumption is to test for the presence of decreasing returns to PSI.…”
Section: Linear and Nonlinear Relationships Between Psi And Performancementioning
confidence: 99%
“…Interestingly, service intensity was measured through manufacturing industry codes. This methodological approach to measure PSI by industry codes has been used in recent work, including Gomes et al (2018) who study the capacity of regions to servitize, Opazo et al (2018) who analyze Digital and Green servitization, Crozet and Milet (2017) who evaluate industry heterogeneity and the positive effect of servitization in profitability, employment and total sales, and Szász et al (2017) who found a linear relationship between PSI and performance with service provision acting as moderator.…”
Section: General Performance: Market Financial Operational…mentioning
confidence: 99%
“…The study by Opazo-Basáez et al [61] in this special issue examines the effect of digital and green servitization on the firm's productivity. The findings show that implementation of digital and green servitization is positively associated with higher productivity outcomes, once these two forms of servitization are made to coexist and operate jointly.…”
Section: Introduction To the Special Issue Contributionsmentioning
confidence: 99%
“…Digitalization is seen as one of the most significant on‐going technological trends faced globally (Hagberg, Sundstrom, & Egels‐Zandén, ). In business settings, it refers to the use of technological advancements to improve customer experience and operational processes, providing the opportunity to create new business models (Fitzgerald, Kruschwitz, Bonnet, & Welch, ; Opazo‐Basáez, Vendrell‐Herrero, & Bustinza, ) through the integration of people, systems companies, products, and services (Hsu, ; Vendrell‐Herrero, Bustinza, Parry, & Georgantzis, ). Through digitalization, companies are able to obtain better visibility for their operations (Yamamoto, ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%